Modern interpretations of Shakespearian Tragedies - Yelik Nursultan, Abzalbek Maxim, Anar Yerkebay, (Opción, 2019)
The purpose of the research is to consider modern interpretations of Shakespearian tragedies by Kazakh, Russian and Georgian theatre directors. The wise combination of different stage readings – the Eastern and European ones – served as a basis of the article effective research method. As a result, each theatre strives to comprehend the high poetry and inherent lyricism of Shakespearian drama and, at the same time, to enhance the social agency and significance of the tragic character. In conclusion, a theatre production may acquire national tints in order to be better understood by the audience.